Exploration of species diversity and vegetation pattern in temperate conifer forests along altitudinal gradients in the Western Himalayas - Hashim, Muhammad; Bushra, Eamon; Dasti, Altaf Ahmad; Abbasi, Asim; Ali, Hayssam M.; Maqsood, Sumaira; Farooq, Taimoor Hassan; Aslam, Asad; Abbas, Zaheer; Khan, Muhammad Tajammal (Frontiers in Forests and Global Change, 2023)
The plant species diversity and distribution pattern are profoundly influenced by edaphic, topographic, and other environmental variables. The current study investigates the species diversity and composition along altitudinal gradients in Western Himalayas, Pakistan. Stratified sampling techniques were employed to collect the vegetation data. A total of 288 quadrates were sampled from 144 stands. The quadrates ranged from 1m2, 5m2, and 10m2 for herbs, shrubs, and trees. Quantitative phytosociological techniques were used to record each species' density, frequency, and cover. Soils sampled from each stand were analyzed for different physic-chemical parameters: pH, electrical conductivity (EC), organic matter (%), nitrogen (N), potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), chlorine (Cl), Carbonates, and Bicarbonates. The vegetation data were analyzed through the Ordination technique using DECORANA Version (MVSP- 3.22). Overall, 154 plant species belong to 50 families, and 131 genera were recorded. Asteraceae (14) was the most represented family, followed by Lamiaceae (12 species), Rosaceae (09), Fabaceae (08 species), Ranunculaceae (06), and Polygonaceae (05). The numerical classification recognized six vegetation associations viz. Senecio chrysanthemoides - Clinopodium piperitum, Artemisia brevifolea - Fragaria nubicola, Parrotiopsis jacquemontiana -Indigofera gerardiana, Micromeria - Viburnum grandiflorum, Siline viscosa - Arisaema propinquum, and Adiantum venustum - Ajuga parviflora. The ordination assessment determined the altitude and edaphic factors (anions, cations) as potential factors to shape the elevational pattern of vegetation distribution. The classification techniques revealed the distinct overlapping rather than discrete boundaries between the vegetation types and species distributions. The overlay of classification to the ordination allowed the interpretations of the vegetation variation in terms of elevation and predictable climatic factors such as rainfall, wind speed, and extent of snow accumulation. The high mountain plant communities experience several anthropo-natural threats advocating the conservation of the coniferous forest under rapid anthropogenic impacts and climate change scenarios. Our results reinforce that species separate through edaphically and landscape scale within the uniform-looking forest. This view maintains that the differences in soil within the forest are distinct enough to favor different species and thus create numerous floristically differentiated forest patches along the altitudinal gradients.